Flow injection chemiluminescence determination of cephalosporins in pharmaceutical preparations using tris (2,2′-bipyridyl) ruthenium (II)-potassium permanganate system - Chalermporn Thongpoon (2018)
A flow injection (FI) method using the tris(2,2′-bipyridyl) ruthenium(II) [Ru(bpy)32+]-potassium permanganate chemiluminescence(CL) was developed for the rapid and sensitive determination of cephalosporins such as cefoxitin, cefazolin, cephalexin, cefadroxil, cefaclor and cefoperazone. The method is based on the CL reaction of cephalosporins and Ru(bpy)32+with potassium permanganate in the presence of perchloric acid, catalyzed by Mn(II). Under the optimum conditions, the calibration curves are linear over the range 0.10-12.0 μg ml-1for cefoxitin, 0.10-10.0 μg ml-1for cefoperazone and 0.10-15.0 μg ml-1for cefazolin, cephalexin, cefadroxil, and cefaclor, respectively. The limits of detection (3σ) are 0.03 μg ml-1for cefoxitin and cefadroxil, 0.06 μg ml-1for cefoperazone and 0.08 μg ml-1for cefazolin, cephalexin and cefaclor, respectively. The method was successfully applied to the determination of cefoxitin, cefazolin, cephalexin and cefadroxil in pharmaceutical formulations with a sample throughput of 90 h-1. There were no interference effects from some common excipients used in pharmaceutical preparations. © 2005 Elsevier B.V. All rights reserved.